PROFIL GAYA HIDUP DAN TEKANAN DARAH PENDUDUK DEWASA DI WILAYAH KERJA PUSKESMAS TIPO PALU TAHUN 2018 (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2019)
An unhealthy lifestyle can cause abnormalities in blood pressure. Smoking habits and lack of physical activity are among the risk factors for disturbances in blood pressure. Smoking habits and lack of physical activity were found to be still high in developing countries such as Indonesia, especially in the City of Palu. The purpose of this study was to describe the profile of adult population lifestyles in the working area of ??Tipo Palu Success in 2018 based on physical activity, smoking habits, blood pressure picture, and knowing the relationship between physical activity and smoking habits with blood pressure. This research is a descriptive and analytic study with cross sectional design in the working area of ??Tipo Health Center for 257 adult residents and conducted from April to June in 2018. Data collection was done by measuring blood pressure along with interviews using a modified IPAQ questionnaire, and smoking habit questionnaire . Data analysis using SPSS 24 to determine the description of lifestyle and blood pressure by frequency test and spearman correlation test. The results showed: (1) the level of physical activity of adult residents in the working area of ??the typo hammer dominant was high physical activity (57.3%), moderate (38.1%) and low (4.6%). (2) according to smoking habits are categories of no smoking (55.4%), then mild smokers (33.8%), moderate smokers (7.3%) and heavy smokers (3.5%). (3) Blood pressure distribution is Normotence (75.5%), Hypertension (22.3%) and Hypotension (1.2%). (4) there is a relationship between physical activity and blood pressure (p = 0,000) (5) there is no relationship between smoking habits and blood pressure (p = 0.325). The adult population in the working area of ??the Tipo Puskemas in Kota Palu, most of them have high physical activity and do not smoke. Hypotension and hypertension sufferers are more common in those who have low to moderate physical activity, and there is no relationship with smoking habits.